2022
DOI: 10.15537/smj.2022.43.2.20210626
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors in women treated for epithelial ovarian cancer in western region of Saudi Arabia

Abstract: Objectives: To assess survival and prognostic factors among women with epithelial ovarian cancer in Western Saudi Arabia.Methods: A retrospective cohort study was carried out between October 2000 and May 2018, reviewing clinical and pathology data of all women who underwent staging or debulking surgery for epithelial ovarian cancer. Analysis of disease-free survival (DFS), overall survivals (OS) and the associated factors used Kaplan-Meier method in addition to cox multivariate regression.Results: A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
2
8
2
Order By: Relevance
“…In a cross-sectional study by Ayub in Pakistan among nursing staff, their ages were between 25-34, and more than two-thirds of nurses (72%) were married [18]. Another result agrees with the present study, which was done in an institution in rural India by Shekhar among nursing staff their age was between (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and most of them (86.6%) were married [19]. The result disagrees with a study done among doctors and nurses indicating the highest percentage of participants their ages were between (21 -30) years old (32.9%) [20].Another that two-thirds of participants (67.9%) were married and their ages were between 41-50 years is also in disagreement with the present study [21].…”
Section: Tablesupporting
confidence: 90%
See 1 more Smart Citation
“…In a cross-sectional study by Ayub in Pakistan among nursing staff, their ages were between 25-34, and more than two-thirds of nurses (72%) were married [18]. Another result agrees with the present study, which was done in an institution in rural India by Shekhar among nursing staff their age was between (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and most of them (86.6%) were married [19]. The result disagrees with a study done among doctors and nurses indicating the highest percentage of participants their ages were between (21 -30) years old (32.9%) [20].Another that two-thirds of participants (67.9%) were married and their ages were between 41-50 years is also in disagreement with the present study [21].…”
Section: Tablesupporting
confidence: 90%
“…The present study has shown more than half (53.3%) of respondents had good knowledge of cervical screening. A similar investigation was reported by Sait [25]. In our study, more than one-third (48.6%) of participants knew that screening should begin at 25 years or 3 years after starting sexual activity whichever is earlier.…”
Section: Tablesupporting
confidence: 89%
“…Vaginal or abdominal routes have been used for hysterectomy procedures conventionally. Laparoscopic hysterectomy is one of the minimal access methods that are being used more often for hysterectomies [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For the last 10 years, the HPV vaccine has been provided in the KSA and is accessible in large hospitals with or without monetary charges [ 11 ]. In KSA, the uptake of the HPV vaccine is still low [ 12 , 13 ], which is attributed to a variety of reasons, including an inadequate understanding of HPV and its connection to cervical cancer, a lack of recognition of the HPV vaccination, and the belief that HPV is a sensitive topic in the conservative Saudi community [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%